2014
DOI: 10.1038/mtm.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

Widespread gene transfer in the central nervous system of cynomolgus macaques following delivery of AAV9 into the cisterna magna

Abstract: Adeno-associated virus serotype 9 (AAV9) vectors have recently been shown to transduce cells throughout the central nervous system of nonhuman primates when injected into the cerebrospinal fluid (CSF), a finding which could lead to a minimally invasive approach to treat genetic and acquired diseases affecting the entire CNS. We characterized the transduction efficiency of two routes of vector administration into the CSF of cynomolgus macaques—lumbar puncture, which is typically used in clinical practice, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
103
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 22 publications
11
103
1
Order By: Relevance
“…We were somewhat surprised the intracerebroventricular injection resulted in such far reaching expression in the CNS, although similar findings have been reported with intra-cerebrospinal fluid injections in mice, pigs, and monkeys (Snyder et al, 2011; Federici et al, 2012; Samaranch et al, 2013; Donsante et al, 2016). We found a mosaic, sporadic labeling of clusters of Purkinje neurons in the cerebellum after intracerebroventricular administration, consistent with other studies (Hinderer et al, 2014; Donsante et al, 2016), which may reflect the flow of the cerebrospinal fluid. In contrast, the intravenous delivery produces more evenly distributed transduction in the cerebellum by comparison.…”
Section: Discussionsupporting
confidence: 92%
“…We were somewhat surprised the intracerebroventricular injection resulted in such far reaching expression in the CNS, although similar findings have been reported with intra-cerebrospinal fluid injections in mice, pigs, and monkeys (Snyder et al, 2011; Federici et al, 2012; Samaranch et al, 2013; Donsante et al, 2016). We found a mosaic, sporadic labeling of clusters of Purkinje neurons in the cerebellum after intracerebroventricular administration, consistent with other studies (Hinderer et al, 2014; Donsante et al, 2016), which may reflect the flow of the cerebrospinal fluid. In contrast, the intravenous delivery produces more evenly distributed transduction in the cerebellum by comparison.…”
Section: Discussionsupporting
confidence: 92%
“…To the editor: Recently, Hinderer et al 1 published the results of a study in cynomolgus macaques that we believe is deserving of comment. In this study, adeno-associated virus serotype 9 expressing green fluorescent protein (AAV9-GFP) was injected intrathecally into these animals at either the lumbar region of the spine or into cisterna magna.…”
Section: Transduction Of Antigenpresenting Cells In the Brain By Aav9mentioning
confidence: 99%
“…To the editor: The recently published paper by Iwahori et al 1 describes the generation of T cells secreting a bispecific anti-CD3 = anti-EphA2 tandem single-chain variable fragment antibody, or BiTE (bispecific T-cell engager). The authors claim that gene-modified T cells secreting bispecific antibodies present a "new class of antigen-specific T cells" with the unique ability to redirect bystander T cells to tumor cells in an antigen-dependent manner.…”
Section: In Vivo Secretion Of Anti-cd3 × Anti-tumor Bispecific Antibomentioning
confidence: 99%
“…1,2 In contrast, direct injection of vector into the cerebrospinal fluid has been shown to achieve high levels of transduction in the CNS. [2][3][4][5] We observed that intrathecal injection of AAV9 into the cisterna magna by suboccipital puncture proved to be very efficient in transducing neurons not only in the brain but also in the spinal cord where motor neurons were the main target. Interestingly, the more distant regions of the spinal cord (thoracic and lumbar areas) showed generally higher levels of motor neuron transduction than cervical areas closer to the injection site.…”
mentioning
confidence: 99%
“…Interestingly, the more distant regions of the spinal cord (thoracic and lumbar areas) showed generally higher levels of motor neuron transduction than cervical areas closer to the injection site. 5 The image (Fig. 1) shows the ventral horn of the lumbar spinal cord from a cynomolgus macaque injected intracisternally with an AAV9 vector expressing GFP from a chicken beta actin promoter at a dose of 5 · 10 12 genome copies/kg.…”
mentioning
confidence: 99%